2019
DOI: 10.3389/fgene.2019.01033
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Coding RNAs in Neurodevelopmental Disorders

Abstract: Non-coding RNAs, a group of ribonucleic acids that are ubiquitous in the body and do not encode proteins, emerge as important regulatory factors in almost all biological processes in the brain. Extensive studies have suggested the involvement of non-coding RNAs in brain development and neurodevelopmental disorders, and dysregulation of non-coding RNAs is associated with abnormal brain development and the etiology of neurodevelopmental disorders. Here we provide an overview of the roles and working mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 111 publications
(144 reference statements)
0
27
0
Order By: Relevance
“…Some examples of ncRNAs and their influential roles in gene regulation or interference include small nuclear RNAs (snoRNAs; RNA splicing), small nucleolar RNAs (RNA modification), miRNAs (RNA degradation and/or translation inhibition), PIWI-interacting RNAs (piRNAs; gene silencing), Y-RNAs (DNA replication), transfer RNAs (tRNAs), and long non-coding RNAs (gene regulation) [ 6 ]. Furthermore, ncRNAs were previously shown to be differentially regulated in neurodegenerative diseases [ 7 ], while others have suggested that its rich repertoire within the human brain makes their involvement and dysregulation potentially crucial in the steps that lead to abnormal brain development and the etiology of neurodevelopmental disorders [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of ncRNAs and their influential roles in gene regulation or interference include small nuclear RNAs (snoRNAs; RNA splicing), small nucleolar RNAs (RNA modification), miRNAs (RNA degradation and/or translation inhibition), PIWI-interacting RNAs (piRNAs; gene silencing), Y-RNAs (DNA replication), transfer RNAs (tRNAs), and long non-coding RNAs (gene regulation) [ 6 ]. Furthermore, ncRNAs were previously shown to be differentially regulated in neurodegenerative diseases [ 7 ], while others have suggested that its rich repertoire within the human brain makes their involvement and dysregulation potentially crucial in the steps that lead to abnormal brain development and the etiology of neurodevelopmental disorders [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression pattern of miRNAs is dynamically regulated during neurogenesis, neuronal differentiation, maintenance and function and overall brain development, making their involvement in neurodevelopmental processes of interest [ 1 , 9 ]. Studies have shown the critical role of alterations in miRNA regulation and signaling in many neurodevelopmental disorders, such as Fragile X syndrome, Rett Syndrome, Down Syndrome, and Prader-Willi Angelman Syndrome [ 8 ]. Since ASD has been associated with several of these conditions, it is interesting to investigate how miRNA dysregulation and/or expression patterns contribute.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed the role of lncRNAs in immunity, specifically in proliferation, differentiation, and activation of immune cells [ 35 ], while their association with CNVs causing ASD is also being studied [ 36 ]. Moreover, microdeletion of snoRNA is associated with neurodevelopmental disorders such as Prader–Willi syndrome-like phenotype [ 37 ]. This highlights the contribution of these ncRNAs in the etiology of diseases and hence emphasizes the need to investigate how SVs might affect their function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to alteration of protein-coding transcripts, abnormalities in splicing patterns as well as ncRNA profiles have been shown in individuals with various psychiatric disorders including ASD (Gandal et al, 2018 ). Specific ncRNA species such as micro RNAs (miRNAs), small nucleolar RNAs, and lncRNAs are involved in psychiatric disorders by regulating transcriptional and translational systems (Zhang et al, 2019 ). Abnormal alternative splicing is also associated with neurodevelopmental disorders (Zhang et al, 2016 ; Gandal et al, 2018 ); for instance, Rbfox1 is a transcription regulator that controls alternative splicing and its mutation is associated with ASD (Wamsley et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%